The new policeman - Thompson, Kate, 1956- (Greenwillow Books, 2007)
Fifteen-year-old musician J.J. Liddy leaves his small, Irish town and travels to the land of the fairies to search for time so he can give it to his busy mother, but when he gets there, he discovers that the inhabitants are in trouble and learns about his family's secret history.